(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
A new stratigraphic unit, the Tabai Limestone of the poorly known Tirah area of northwest Pakistan, is one of several Early Carboniferous carbonate units distributed along the North Gondwana margin, some connected with transgressive interludes. The Tabai Limestone has produced latest Tournaisian (Early Carboniferous) conodonts indicative of the middle of the anchoralis-latus Zone.